2017
DOI: 10.1016/j.cedpsych.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ autonomous functioning and implicit theories of ability as predictors of their school achievement and week-to-week study regulation and well-being

Abstract: a b s t r a c tResearch on students' motivation has mainly focused on interpersonal differences rather than on the ongoing, intrapersonal dynamics that forge students' everyday life. In this five-month longitudinal (diary) study, we recruited a sample of 179 high school students from Greece (35.8% males; M age = 16.27; SD = 1.02) to investigate through multilevel analyses the ongoing dynamics of students' motivation. We did so by examining the relation between autonomous functioning and aspects of study regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 64 publications
(93 reference statements)
7
33
0
4
Order By: Relevance
“…Although the relationships were relatively small, they were in line with the effect sizes reported in previous research (e.g. Gonida et al ., ; Da Fonseca et al ., ; Romero et al ., ; Mouratidis et al ., ), and were present in both English and Maths performance, indicating that believing in the malleability of intelligence may play a role in improved outcomes across subjects. It was also found that measures of gender, FSM eligibility and SEN status were all related to attainment in Maths and English in the expected direction, with girls attaining higher than boys, and eligibility for FSM and SEN status being associated with lower attainment.…”
Section: Discussionmentioning
confidence: 93%
“…Although the relationships were relatively small, they were in line with the effect sizes reported in previous research (e.g. Gonida et al ., ; Da Fonseca et al ., ; Romero et al ., ; Mouratidis et al ., ), and were present in both English and Maths performance, indicating that believing in the malleability of intelligence may play a role in improved outcomes across subjects. It was also found that measures of gender, FSM eligibility and SEN status were all related to attainment in Maths and English in the expected direction, with girls attaining higher than boys, and eligibility for FSM and SEN status being associated with lower attainment.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Yeager, Trzesniewski, Tirri, Nokelainen, and Dweck (2011) discussed the negative role in attribution of a fixed mindset and the positive role of intervention in emotion with a growth mindset. Moreover, some of the studies reviewed (e.g., Cury et al, 2008;Zeng et al, 2016;Mouratidis et al, 2017) indicated that attributions and emotions were important mediators between mindset and achievement. Secondly, we excluded studies that were not written in English.…”
Section: Discussionmentioning
confidence: 99%
“…A Greek study indicated that mindset was found to moderate the week-to-week relation of autonomous functioning to study effort and homework procrastination; it also affected student well-being, such as subjective vitality, and feelings of depression and thereby had a direct influence on academic achievement (Mouratidis et al, 2017). For example, a fixed mindset demonstrated lower mean levels of study effort, higher amounts of homework, and poorer grades.…”
Section: Mindset As a Mediatormentioning
confidence: 99%
“…Prior research has provided evidence for the positive link between autonomous functioning and study effort (e.g. Liu et al, 2014;Mouratidis, Michou, & Vassiou, 2017) as autonomous motivation is more likely to propel students to exert effort in their studies even in the face of difficulties (León et al, 2015).…”
Section: The Present Researchmentioning
confidence: 99%